2021
DOI: 10.1101/2021.08.26.457800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leaked genomic and mitochondrial DNA contribute to the host response to noroviruses in a STING-dependent manner

Abstract: The cGAS-STING pathway is central to the IFN response against DNA viruses. However, recent studies are increasingly demonstrating its role in the restriction of some RNA viruses. Here we show that the cGAS-STING pathway also contributes to the IFN response against noroviruses, positive-sense single-stranded RNA viruses that are now one of the most common causes of infectious gastroenteritis world-wide. We show a significant reduction in IFN-β induction and a corresponding increase in viral replication in norov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…To generate the relevant lentiviruses, the untagged pSMPP-TRIM7 constructs were co-transfected into HEK293T cells with pMDG2 (a gift from D. Trono [EPFL; Addgene, plasmid 12259]) and pCRV-GagPol (a gift from S. Neil, Kings College London) plasmids using FuGENE6 (Promega) reagent and incubated for 3 days. Supernatants were harvested by filtration and used for transduction of HeLa cells expressing the mouse CD300lf [ 28 ] as previously described [ 20 ]. Briefly, 2.5 × 10 5 cells were infected with the appropriate lentivirus in a 6-well plate in DMEM supplemented with 3% FBS, 20 mM HEPES and 4 μg/mL Polybrene, and spinoculated at 1000× g and 25 °C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…To generate the relevant lentiviruses, the untagged pSMPP-TRIM7 constructs were co-transfected into HEK293T cells with pMDG2 (a gift from D. Trono [EPFL; Addgene, plasmid 12259]) and pCRV-GagPol (a gift from S. Neil, Kings College London) plasmids using FuGENE6 (Promega) reagent and incubated for 3 days. Supernatants were harvested by filtration and used for transduction of HeLa cells expressing the mouse CD300lf [ 28 ] as previously described [ 20 ]. Briefly, 2.5 × 10 5 cells were infected with the appropriate lentivirus in a 6-well plate in DMEM supplemented with 3% FBS, 20 mM HEPES and 4 μg/mL Polybrene, and spinoculated at 1000× g and 25 °C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…[76][77][78] Similarly, researchers revealed that plasmid DNA transfection activates the cGAS-STING pathway, preparing the cells to be in an antiviral state that compromises the infectivity of coxsackievirus B3 (CVB3). 79 The cGAS-STING pathway also robustly evokes IFN response and effectively inhibits infection of several other RNA viruses, including chikungunya virus (CHIKV), 80,81 encephalomyocarditis virus (EMCV), 68,71 hepatitis C virus (HCV), 82 influenza A virus (IAV), 71,83 measles virus (MeV), 84,85 murine norovirus (MNV), 86,87 Nipah virus (NiV), 84 and Zika virus (ZIKV). 88 Surprisingly, in addition to antiviral role, STING has been discovered to be proviral in rare cases of RNA viral infections.…”
Section: Role Of Cgas-sting Pathway In Rna Viral Replicationmentioning
confidence: 99%
“…71 A number of studies have reported that RNA viral infection can induce mtDNA leakage, consequently prompting the activation of the cGAS-STING axis. For example, infection with CHIKV, 81 DENV, 64,65 IAV, 71 MeV, 85 and MNV 86 EMCV infection, respectively, in a mitochondrial antiviral signalling (MAVS)-dependent manner. 71 (Figure 2).…”
Section: Mechanisms By Which Rna Viruses Activate the Cgas-sting Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…To generate TRIM7 lentiviruses pSMPP-hTRIM7 constructs were co-transfected into HEK293T cells with pMDG2 and pCRV-GagPol plasmids using FuGENE6 (Promega) reagent and incubated for 3 days. Supernatants were harvested by filtration and used for transduction of HeLa cells expressing the mouse CD300lf (Jahun et al, 2021) as previously described (Fan et al, 2021). Briefly, 2.5E5 cells were infected with the appropriate lentivirus in a 6-well plate in DMEM supplemented with 3% FBS, 20 mM HEPES, and 4 µg/ml Polybrene, and spinoculated at 1000 × g and 25°C for 45 min.…”
Section: Stable Cell Line Generationmentioning
confidence: 99%